ENVIRONMENTAL POLICIES AND TRADE COMPETITIVENESS: THE MALAYSIAN PALM OIL DOWNSTREAM INDUSTRY - Norashida Othman; Zulkornain Yusop; Mohd Mansor Ismail (International Journal of Business and Society, 2023)
This paper explore how export competitiveness in the Malaysian palm oil downstream industry is affected by European Union (EU) environmental regulation. Porter (1990) suggests that environmental policies may foster international competitiveness. To investigate the impact of EU environmental policies on trade competitiveness in the Malaysian palm oil downstream industry, the dynamic generalized method of moments (DGMM) is employed. The final results reveal that EU environmental regulations have a positive impact on palm oil industry competitiveness. This result is consistent with the Porter Hypothesis, which argues that a more stringent environmental regulation can trigger innovation to non-compliance cost. Palm oil downstream innovation is crucial to improve the overall competitiveness of the industry, including the smallholders’ sector. This implies that the Malaysian government may want to introduce certain measures, such as energy taxes to promote the use of renewable energy. This may lead to more sustainable palm oil production which may improve the overall competitiveness of the palm oil downstream industry.